Correlation of histologic grade of breast carcinoma with hormone receptor status in a tertiary care hospital - George, Greeshma Ann; Bembde, Archana Sachin; Borde, Neha; Bhale, Chandrashekhar (International Journal of Research in Medical Sciences, 2018)
Background: Breast cancer is one of the most common malignancies affecting the female population worldwide. Prognosis and management of breast cancer are influenced by variables such as stage, grade, hormone receptor status of oestrogen(ER), progesterone(PR) and Human epidermal growth factor receptor2 (HER2/neu) overexpression. Aim to correlate grade of tumour with ER, PR and HER2/neu receptor status of breast carcinoma. Methods: A prospective study was done in Pathology department, MGM Medical College and Hospital, Aurangabad, Maharashtra for one year. Out of 65 cases studied, 28 cases were biopsy and 37 cases were modified radical mastectomy specimens. All samples were subjected for routine histological examination and immunohistochemical analysis. Results: Age of patients ranged from 30 to 82 years; 60% of tumours were right sided; 46% were involving upper outer quadrant; 58% were radiologically BI-RADS 4; 46% tumours were histopathologically grade 2 and 90% were invasive breast carcinoma, not otherwise specified. By immunohistochemistry, 60% were ER/PRpositive, 9% HER2/neu positive, 26% triple negative and 5% HER2/neu equivocal. In our study, out of 13 grade 1 tumours, 100% were ER/PRpositive and HER2/neu negative; thus an inverse relationship was found between HER2/neu and ER/PR receptors. Also 70% of triple negative tumours were grade 3 which have an aggressive behaviour compared to other subtypes and were common in premenopausal women. Conclusions: Assessment of hormone receptors for clinical management of breast cancer patients is strongly advocated to provide prognostic information and best therapeutic options. A significant correlation was observed between hormonal receptor status and the grade of tumour.